10.38: Effects of heat‐treatment methods on mechanical performance of high‐tensile strength steel subject to elevated temperatures. (13th September 2017) - Du, Yong; Liew, J. Y. Richard; Xiong, Ming‐Xiang
ABSTRACT: This study is motivated by increasingly prevalent use of high tensile‐strength steel (HTS) in constructions, where fire is one of the extreme conditions that need to be taken into account in design phase. Previous studies showed lack of awareness regarding the effects of heat‐treatment methods on temperature dependent mechanical properties of the HTS. With this research gap being identified, standard tensile tests for Grade S690 steels made from Quench‐Temper (QT) Process and Thermo‐Mechanically Controlled Process (TMCP) were conducted. Transient‐state were adopted. The mechanical properties were compared and their differences were discussed. In General, the elastic moduli were similar for HTSs from different heat‐treatment methods, but the effective yield strength of TMCP‐S690 deteriorated more than that of QT‐S690 at elevated temperatures.